2004
DOI: 10.1103/physrevlett.93.155003
|View full text |Cite
|
Sign up to set email alerts
|

Ion Acceleration by Collisionless Shocks in High-Intensity-Laser–Underdense-Plasma Interaction

Abstract: Ion acceleration by the interaction of an ultraintense short-pulse laser with an underdense-plasma has been studied at intensities up to 3 x 10(20) W/cm(2). Helium ions having a maximum energy of 13.2+/-1.0 MeV were measured at an angle of 100 degrees from the laser propagation direction. The maximum ion energy scaled with plasma density as n(0.70+/-0.05)(e). Two-dimensional particle-in-cell simulations suggest that multiple collisionless shocks are formed at high density. The interaction of shocks is responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
55
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(65 citation statements)
references
References 17 publications
6
55
2
Order By: Relevance
“…In 2000s, experiments on ion acceleration in the radial direction to the incident high-intensity laser beam by a radial collisionless ES shock in an underdense plasma have been reported [71][72][73]. Nilson et al have reported the experimental generation of high Mach-number ES shock in an underdense plasma with a high-intensity laser beam [74], with an experimental condition similar to that in [72].…”
Section: Introductionmentioning
confidence: 93%
“…In 2000s, experiments on ion acceleration in the radial direction to the incident high-intensity laser beam by a radial collisionless ES shock in an underdense plasma have been reported [71][72][73]. Nilson et al have reported the experimental generation of high Mach-number ES shock in an underdense plasma with a high-intensity laser beam [74], with an experimental condition similar to that in [72].…”
Section: Introductionmentioning
confidence: 93%
“…The acceleration of electrons in the interaction of a high-intensity laser beam with plasma may have important applications in various domains such as laser particle acceleration, ion acceleration for fusion action, and the generation of intense and short-duration cray sources for radiography [4][5][6]. Furthermore, the interaction of an ultra short high-intensity laser pulse with plasma without external dc magnetic field has been studied extensively [7][8][9][10][11]. When an external magnetic field is applied to the plasma, it is a medium capable to convert different initial energies to tunable coherent radiations.…”
Section: Introductionmentioning
confidence: 99%
“…In intense laser interaction with solid targets, several schemes for realizing highly energetic ion bunches have been proposed and demonstrated. These include target normal sheath acceleration ͑TNSA͒, 1-5 collisionless electrostatic shock acceleration, [6][7][8] breakout afterburner acceleration, 9,10 radiation pressure acceleration ͑RPA͒, [11][12][13] etc. Besides of basic physical interest, laser-driven ion bunches can be useful in many novel applications, including ion-beam tumor therapy, 14 proton imaging, 15 injectors for standard accelerators, 16 ion-beam ignition in inertial confinement fusion, 17 etc.…”
Section: Introductionmentioning
confidence: 99%